Hubungan Persepsi Ibu Tentang Sarana Pelayanan KIA Dengan Kun- jungan Pemeriksaan Kehamilan (K4) (Studi di Wilayah Kerja Puskesmas Tegal Barat II Kota Tegal Tahun 2006) - Cahya Tri Purnami; Rizki Anna L (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2007)
Background: Maternal and Child Care is one of factors to reduce Maternal Mortality Rate. This service needs sufficient supports, i.e. antenatal care guideline, health personnel, and its facilities. A pregnant mother is required to have a minimum of 4 times of Antenatal Care within her pregnancy, i.e. 3rd month, 6th month, 7th and 9th month. Compared to other health centers, Tegal Barat II Health Center recorded lower rate on Antenatal Visitors Rate or about 60%. Meanwhile, the national standard requires 90% of Antenatal Visitors Rate. This research aimed to explain the association between maternal perception on maternal and child carefacilities and antenatal care (K4).Method: This research was an explanatory research, utilizing cross sectional approach. Forty five respondents were taken from mothers who have babies less than 3 months old and visited the health centers. Questionnaires were utilized to gather the data, and the analysis wasconducted based on descriptive as well as analytic.Result: Result showed that out of 45 respondents: 53.3% had perception that antenatal guideline book was not interesting, 17.8% said that health personnel had to examine fundus height metrically, and 93.3% said that all pregnant women had to obtain Fe tablets from health center. Variables that significantly associated with antenatal care (K4) were maternal perception on antenatal care guideline (at p-value: 0.012) and maternal perception on antenatal care facilities (at p-value: 0.0001). Meanwhile, maternal perception on health personnel (at p-value: 0.161) was not associated with antenatal care. It was concluded and recommendedthat the performance of Antenatal Care Guideline and Antenatal Care Facilities must be improved.Keywords: Antenatal care, service quality.